In Vitro and In Vivo Characterization of Scleral Implant of Indomethacin: Role of Plasticizer and Cross-Linking Time - Kumar M.T.; Rajeswari C.; Balasubramaniam J.; Pandit J.K.; Kant S. (My University, 2025)
Film-type scleral implants of indomethacin using sodium alginate and PEG 400 and 600 (3, 5, 8, and 10% w/w w.r.t. sodium alginate) as plasticizers were fabricated by solvent casting. The prepared implants were cross-linked by treatment with calcium chloride 10, 20, and 30% w/v solution, for periods between 1 to 24 hr. Uniformity of thickness, weight, and drug content and surface pH of the implants were evaluated. The influence of plasticizer type/concentration and crosslinking time/concentration of calcium chloride on indomethacin release was studied on a static dissolution setup developed by us. Selected batches of the implants were subjected to pharmacodynamic studies, after scleral placement, in uveitis-induced (intravitreal injection of bovine serum albumin 50 μg/ml) rabbit eyes. The release of indomethacin from the implants was influenced by the concentration and nature of plasticizers used. Chemical cross-linking with calcium chloride was successful in retarding the drug release. The pharmacodynamic studies showed a marked improvement in the various clinical parameters (congestion, keratitis, flare, clot, aqueous cells, and synechias) in the implanted eye when compared with the control eye in the rabbits. The implants survived for 2 weeks in vivo.